Continuous measurements of stable isotopes of carbon dioxide and water vapour in an urban atmosphere: isotopic variations associated with meteorological conditions. Issue 6 (2nd November 2017) - Wada, Ryuichi; Matsumi, Yutaka; Nakayama, Tomoki; Hiyama, Tetsuya; Fujiyoshi, Yasushi; Kurita, Naoyuki; Muramoto, Kenichiro; Takanashi, Satoru; Kodama, Naomi; Takahashi, Yoshiyuki
ABSTRACT: Isotope ratios of carbon dioxide and water vapour in the near-surface air were continuously measured for one month in an urban area of the city of Nagoya in central Japan in September 2010 using laser spectroscopic techniques. During the passages of a typhoon and a stationary front in the observation period, remarkable changes in the isotope ratios of CO2 and water vapour were observed. The isotope ratios of both CO2 and water vapour decreased during the typhoon passage. The decreases can be attributed to the air coming from an industrial area and the rainout effects of the typhoon, respectively. During the passage of the stationary front, δ 13 C–CO2 and δ 18 O–CO2 increased, while δ 2 H–H2 Ov and δ 18 O–H2 Ov decreased. These changes can be attributed to the air coming from rural areas and the air surrounding the observational site changing from a subtropical air mass to a subpolar air mass during the passage of the stationary front. A clear relationship was observed between the isotopic CO2 and water vapour and the meteorological phenomena. Therefore, isotopic information of CO2 and H2 Ov could be used as a tracer of meteorological information.